THE ERRORS OF USING ADVERBS BY THE ELEVENTH YEAR STUDENTS OF SMA NEGERI 7 MEDAN - Merlin Helentina Napitupulu (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
This thesis explores about the errors of using adverbs by the eleventh year students of SMA Negeri 7 Medan. The purpose of this thesis is to analyze how the students use adverbs and identify the errors into four kinds of errors based on Rod Ellis (1997) says there are four kinds of errors: misinformation, misordering, omission and overgeneralization. The result of the research can be concluded that the most dominant errors done by students is using adverb of manner in type of overgeneralization 15.49%.Key words: using adverbs, kinds of errors